(untitled) (Progressive Agriculture, 2013)
An experiment was conducted to study the efficacy of Malathion at different doses against red pumpkin beetle, Aulacophora foveicollis (Lucas) in Field Laboratory of the Department of Entomology, Bangladesh Agricultural University, Mymensingh. Three cucurbit hosts such as sweet gourd (Var. BARI sweet gourd1), bitter gourd (Var. Hybrid Nepali) and bottle gourd (Var. Kajla) were selected to conduct the research with three different doses viz. 0.4%, 0.5% and 0.6% of Malathion. Among the three doses of Malathion it was revealed that minimum number of leaf attack per plant, number of twig attack per plant, and average leaf area damage by red pumpkin beetle was found when the plants were treated with 0.5% and the maximum damage was observed in case of 0.4% Malathion application. The efficacy of the insecticide reduced with increasing time intervals of spraying. Considering the efficacy in reducing the leaf area damage at all the time intervals spraying 5% Malathion was found as the most effective in controlling red pumpkin beetle in three different cucurbit hosts. The efficacy of Malathion was similar on three different cucurbit hosts. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16462 Progress. Agric. 22(1 & 2): 11 - 18, 2011